Pigeons (Columba livia domestica) Are Susceptible to Infectious Bursal Disease: A Comparative Study of Their Hematological and Serum Biochemical Alterations - Orakpoghenor, Ochuko; Oladele, Sunday Blessing; Abdu, Paul Ayuba; Markus, Talatu Patience; Enam, Samson James; Andamin, Aliyu Danlami; Muhammed, Muhammed Shuaib; Usman, Suleman Geidam; Esievo, King Akpofure Nelson (Frontiers in Veterinary Science, 2021)
The hematological and serum biochemical alterations following very virulent infectious bursal disease virus (IBDV) infection in pigeons and chickens were evaluated in this study. Sixty IBDV seronegative birds comprising 30 (3–6 weeks old) pigeons and 30 (3 weeks old) chickens were randomly divided as follows: 10 uninoculated pigeons only, 10 inoculated pigeons + 10 sentinel chickens, 10 inoculated chickens + 10 sentinel pigeons, and 10 uninoculated chickens. Inoculated birds were administered 0.20 ml of inoculum containing very virulent IBDV (vvIBDV). Blood was collected postinoculation/exposure (pi/pe) and processed for hematology and biochemistry. The results revealed significantly (P < 0.05) increased packed cell volume, decreased mean corpuscular hemoglobin (MCH), and MCH concentration (MCHC) in inoculated and sentinel chickens. Total leukocyte count (TLC), heterophil, and heterophil/lymphocyte (H/L) ratio were increased from 3 dpi/dpe in inoculated pigeons and from 3 to 14 dpi/dpe in inoculated and sentinel chickens. At 10 and 14 dpi/dpe, there was significantly (P < 0.05) increased serum total protein and globulin concentrations and decreased albumin/globulin ratio in pigeons and chickens. Serum urea concentration showed significant (P < 0.05) increase in inoculated and sentinel chickens at 3 and 4 dpi/dpe. To the authors' knowledge, this is the first report on hematological and serum biochemical alterations due to vvIBDV infection in pigeons.